Research on DSP-based Asynchronous Motor Control Technology - Jun Yao; Xiangxin Qiao; Xin Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The Motor in a variety of electrical transmission and position servo system occupies an extremely important position. After the DSP technology being applied to the motor control, the unification of the hardware and the flexibility of the software can be combined. Take the brushless DC motor for example, studied the mathematical model and the structure of the motor control system, also obtained the design scheme of the DSP-based asynchronous motor control system. With TI's 32 bit fixed point DSPTMS320F2812 as the core design of the hardware system, we wrote the system software, debug the motor control system and the results show that the system achieves the expected effect. The results of the research can be applied to brushless DC motor and other motor control, it will have a wide application prospects. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2565